The Effect of Vitamin C Consumption on Increasing Hemoglobin and Ferrithin Levels of Pregnant Anemia Who Receive Blood Supplements - Gita Rahmadani; Almurdi Almurdi; Endrinaldi Endrinaldi (Institute of Computer Science (IOCS), 2021)
Anemia in pregnancy is a problem that frequently occurs in pregnant women. It is a national health problem that will affect human resources in the future. Supplements in the government program to overcome the problem of anemia are by giving blood-added tablets and should be combined with vitamin C. The objective of this study was to determine the effect of vitamin C consumption on increasing hemoglobin and ferritin levels in pregnant women with anemia who received blood supplement tablets. This is a quasi-experimental design that uses a pretest and posttest approach with a control group. The research was conducted at the Pauh Public Health Center and the Health Laboratory Center. Data collection was carried out on January 02 – March 03 on 34 pregnant women with TM III who had anemia who were divided into two groups. Ferritin levels were checked by using ECLIA method and hemoglobin levels by a hematology analyzer. Normality test was done by using Shapiro Wilk and continued with T-test T-Independent and Dependent Test. The results showed that the average hemoglobin level before vitamin C consumption in the intervention group was 10.32 g/dL and the control group was 10.15 g/dL. Ferritin levels before the intervention group was 13.23 g/mL and the control group was 13.06 g/mL. Hemoglobin level after intervention was 11.75 g/dL and control 11.36 g/dL. Ferritin levels after intervention were 57.37 g/mL and control 50.91 g/mL. The results of the statistical test showed no difference in the increase in hemoglobin levels with a p value of 0.194 and a ferritin level with a p value of = 0.367 between the intervention and control groups. The conclusion in this study is that there was no difference in the increase in hemoglobin and ferritin levels of anemic pregnant women after consuming vitamin C between the intervention and control groups.